Understanding long‐term effects of topsoil removal in peatlands: overcoming thresholds for fen meadows restoration. Issue 1 (9th September 2014) - Klimkowska, Agata; van der Elst, David J.D.; Grootjans, Albert P.; Middleton, Beth
Abstract Questions What are the long‐term results of fen meadow restoration after topsoil removal on peatlands? What are the causes of slow fen‐meadow vegetation recovery on peat soils after topsoil removal? Location Drentsche Aa Nature Reserve (53°00′49″N, 6°37′46″E) in the northeast Netherlands, with extensive natural and partially restored fen meadows (ca. 10, 000 ha). Methods Restoration measures consisted of removal of acidified and fertilized topsoil and improvement of local hydrology by blocking or removing drainage ditches. The effects of shallow (20 cm) and deep (40 cm) topsoil removal were compared. We monitored vegetation changes after restoration measures in permanent plots over a 13‐yr period, and analysed changes in species composition over time with ordination techniques (multivariate analysis: PCA and RDA). Soil conditions over time were analysed using repeated measures ANOVA. Results The vegetation and environment shifted over time in response to restoration. At first the vegetation stagnated in a species‐poor phase for 5 yr, but eventually fen‐meadow species re‐established. At the end of the observation period, after 14 yr, the vegetation after both shallow and deep peat removal was similar. Soil acidification occurred immediately after topsoil removal (within the first 2–3 yr) due to pyrite oxidation when the soil was exposed to air after site excavation and the peat was temporarily desiccated. Conclusions We found poor re‐establishment of fen‐meadow vegetation and persistence of species‐poor communities during the first 5 yr after topsoil removal, probably resulting from internal soil acidification. After further rewetting, a rapid shift towards the target community composition was observed. The positive shift in development of fen‐meadow vegetation probably occurred due to increased groundwater discharge after successful hydrological measures were applied. Appropriate hydrological conditions (strong discharge of groundwater) are important for the success of restoration of these fen meadows, especially if pyrite is present in shallow soil layers.